Pendampingan Penyusunan Sistem Akuntansi Penerimaan Kas Pada Toko Bangunan Kembar Jaya Di Kabupaten Sorong - Sandi H Pasaribu (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Community service is carried out with the aim of providing cash knowledge and practice of the accounting system for cash receipts and cash sales at the Kembar Jaya Building Store. Especially regarding cash receipts and cash sales with Cash Over the Counter Sale. This service activity is carried out for shop owners who have over the counter cash sales transactions. This activity will provide additional knowledge and practice in handling cash receipts from cash sales with Cash Over the Counter Sale of merchandise. The hope that will be obtained in this service is that the shop owner knows and can handle his business transactions. With a cash receipt system from cash sales, there is adequate internal control and the owner can control his business activities well. The method used in this activity is by providing learning in the form of mentoring and manually preparing a cash receipt system from cash sales with Cash Over the Counter Sale. Keywords: Accounting System, Cash Receipts and Cash Sales